TINJAUAN PENERAPAN KESEHATAN DAN KESELAMATAN KERJA (K3) TERHADAP PETUGAS REKAM MEDIS PADA RUANG PENYIMPANAN DI RSAU Dr. M. SALAMUN BANDUNG - Suharto, Suharto; Alhadar, Nawira Qalbina; Purba, Asmat (Jurnal TEDC, 2023)
This preliminary study is motivated by the fact of medical rocords storage room of the RSAU dr. M. SALAMUN’S lack of ergonomics include: medical records files storage has a leaky roof and the sink is very close to the storage rack, gloves are not provided, and the lack of personal protective equipment. The author conducted research using qualitative method with a descriptive approach. Data collection Technique by means of observation, interview, documentation and literature study.The results of the authors research are the storage area 42 m2 with details of length 7 m, width 6 m and has height of 3 m. The distance between the open shelves that is 79 cm and based on the results obtained are said to be inconsistent. The standard spacing between shelves, which is 80cm - 200cm. An imbalance between storage space and the distance between shelves and the ventilation entrances that are lacking, causing inconvenience to staff The author also suggest that the arrangement of the room, setting the distances between shelves consistently improving ventilation, providing personal protective equipment that is easy to use by staff, request for storage of shelves to the general area as quickly as possible, continue to improve the effectiveness of work so that it runs well and smoothly.